On Some Genres of Biblio-painting - N. S. Murashova (Библиосфера, 2024)
Biblio painting is considered as a segment of the bibliosphere and as one of the areas of world fine art. Genres are identified in which the book acts as an artistic image, that carries an important semantic load, and is also used as a significant element of the composition. These genres include religious, mythological, allegorical, everyday painting, works on literary subjects, portraits and biblio still lifes. The aim of the article is to present the history of interpretation of art book image in the works of religious (Christian), mythological, allegorical painting as well as easel paintings, made on the bases of literary works. It is concluded that the development of biblio-painting correlates with the peculiarities of the transformation of book culture itself, since the interpretation of the artistic image of a book in pictorial genres emphasizes their integration into the bibliosphere as a whole.